2016
DOI: 10.1111/ajt.13537
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Subpopulation of Bone Marrow Mesenchymal Stem Cells, Muse Cells, Directly Commit to the Replacement of Liver Components

Abstract: Genotyping graft livers by short tandem repeats after human living-donor liver transplantation (n ¼ 20) revealed the presence of recipient or chimeric genotype cases in hepatocytes (6 of 17, 35.3%), sinusoidal cells (18 of 18, 100%), cholangiocytes (15 of 17, 88.2%) and cells in the periportal areas (7 of 8, 87.5%), suggesting extrahepatic cell involvement in liver regeneration. Regarding extrahepatic origin, bone marrow mesenchymal stem cells (BM-MSCs) have been suggested to contribute to liver regeneration b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 36 publications
3
65
0
1
Order By: Relevance
“…Recently, Katagiri and colleagues observed that a small representation (1–2%) of bone marrow mesenchymal stem cells, named Muse, differentiate into liver-lineage cells and repair tissue. After their infusion in a model of partial hepatectomy, they integrated into regenerating areas and expressed liver progenitor markers during the early phase of regeneration to then differentiate into hepatocytes, KC and LSEC [89]. Muse cells can be obtained easily from patients and donors, and could be used for clinical applications.…”
Section: - Sinusoidal Crosstalk In Liver Regeneration and Transplantmentioning
confidence: 99%
“…Recently, Katagiri and colleagues observed that a small representation (1–2%) of bone marrow mesenchymal stem cells, named Muse, differentiate into liver-lineage cells and repair tissue. After their infusion in a model of partial hepatectomy, they integrated into regenerating areas and expressed liver progenitor markers during the early phase of regeneration to then differentiate into hepatocytes, KC and LSEC [89]. Muse cells can be obtained easily from patients and donors, and could be used for clinical applications.…”
Section: - Sinusoidal Crosstalk In Liver Regeneration and Transplantmentioning
confidence: 99%
“…All statistical analyses were performed using StatView version 5.0 (SAS Institute Inc., Cary, NC, USA). 7 …”
Section: Muse Cell Number In the Peripheral Bloodmentioning
confidence: 99%
“…The proportion of Muse cells in the BM-mononucleated cells is ~0.03%, so that ~30 ml bone marrow aspirate yields approximately 1 million Muse cells by ~3 days 11 . Intravenously injected naive Muse cells migrate to and integrate into damaged sites and spontaneously differentiate into functional cells in injury models of the liver, muscle and skin 11,14 . Grafted Muse cells contribute to tissue reconstruction in skin ulcers of a diabetes mellitus model by replenishing new dermal and epidermal cells; similarly human skin fibroblast-derived Muse cells rebuild pyramidal and sensory tracts by replacing new functional neuronal cells in the cortex that could extend neurites into the contralateral spinal cord and physiologically evoke firing potentials 1517 .…”
Section: Introductionmentioning
confidence: 99%